Adjuvants MPLA and SMNP induce antiviral immunity and indirectly revert HIV-1 latency - Jade Jansen; Killian E. Vlaming; Leanne C. Helgers; Eva Schumacher; Tanja M. Kaptein; Rogier W. Sanders; Godelieve J. de Bree; Teunis B.H. Geijtenbeek; Neeltje A. Kootstra (PLoS ONE, 2026)
Monophosphoryl lipid A (MPLA) and the saponin-MPLA nanoparticle adjuvant (SMNP) are known immunostimulants used as adjuvants in vaccines to boost immunity. These adjuvants are under investigation for use in prophylactic and therapeutic HIV-1 vaccines. However, their effects in ART-treated people with HIV-1 (PWH) remain unclear, as chronic immune activation may reduce responses and potentially reactivate latent virus reservoirs. Here we observed that both adjuvants, MPLA and SMNP, triggered TLR4‑dependent cytokine production in monocyte-derived dendritic cells (DCs), but SMNP elicited a stronger response than MPLA based on costimulatory receptor expression and cytokine production. Cytokines produced by adjuvant stimulated dendritic cells were able to induce HIV-1 transcription in a J-Lat cell model. Notably, SMNP, but not MPLA, also induced a cytokine response in PBMC from PWH, albeit lower as compared to in healthy donor PBMC. Importantly, SMNP substantially reduced the size of the inducible HIV‑1 reservoir in PWH ex vivo . The effect on the viral reservoir was likely caused by the cytokine production induced by SMNP, as supernatants from SMNP stimulated DCs showed a similar viral reservoir reduction. Our findings demonstrate that TLR4-targeted adjuvants, especially SMNP, can effectively induce immune activation, supporting their potential use in therapeutic vaccination.